Agreement Benefits and Function Analysis in Marriage - Susi Imro Atul Rizqiati; Yunanto (IHSA Institute, 2022)
The marriage agreement is a means to protect the property of the bride and groom. Through this agreement, the parties can determine their respective assets. Marriage agreements are also for the people of Indonesia is an unusual thing even though it has been regulated in the Marriage Law. This is because, the problem of marriage can’t be separated from customs. An understanding based on traditional thinking that marriage is a bond that cannot be separated/broken except for death by the will of God Almighty. The type of research used in this paper is normative legal research. The approach used by the author is a statute approach. The data sources in this study are divided into two, namely primary law and secondary law. The method used to collect legal materials is through literature study to make a marriage agreement, the parties, in this case the husband and wife who carry out the marriage, are free to determine the desired legal form for the assets that are the object. The marriage agreement is not an obstacle in marriage but can actually help in marriage. However, in order to be useful, the making of the agreement must be in accordance with the applicable legal rules or regulations. The marriage agreement has a useful value for the parties to the marriage. Apart from being a legal protection for the parties, the marriage agreement also provides benefits in the event of a conflict in the court institution when a divorce occurs.